Components of the Mediterranean Diet and Risk of COVID-19 - Perez-Araluce, Rafael; Martínez-González, Miguel Ángel; Gea, Alfredo; Carlos, Silvia (Frontiers in Nutrition, 2022)
Adherence to the traditional Mediterranean diet has been customarily assessed with the Mediterranean Diet Score (MDS, Trichopoulou, 2003) with values of 0 or 1 assigned to each of 9 elements, with the use of the sex-specific median as the cutoffs. Persons whose consumption of 6 beneficial items (ratio of monounsaturated to saturated fatty acids, vegetables, legumes, fruits and nuts, cereal, and fish) is at or above the median are assigned a value of 1. Otherwise they receive 0 points. For detrimental elements (meats and dairy products) persons whose consumption is below the median are assigned a value of 1. An additional ninth point is assigned to moderate ethanol intake. We assessed the effect of each of the 9 components of the MDS (replacing the fats ratio with olive oil, the main source of monounsaturated fats in the Mediterranean diet) on the risk of COVID-19 infection, symptomatic and severe COVID-19. From February to December 2020, 9,699 participants of the “Seguimiento Universidad de Navarra” (SUN) cohort answered to a COVID-19 questionnaire. After excluding doctors and nurses, 5,194 participants were included in the main statistical analyses. Among them, we observed 382 cases of COVID-19 based on symptoms and clinical diagnosis; 167 of them with test confirmation. For the two COVID-19 definitions used, we found a significant decrease in risk for a higher adherence to the Mediterranean diet (OR = 0.64, 95% CI: 0.42-0.98, p for trend = 0.040; and OR = 0.44, 95% CI: 0.22- 0.88, p for trend = 0.020, for test-diagnosed cases). A protective effect was also found for symptomatic COVID-19 (OR = 0.64, 95% CI: 0.41-1.00, p for trend = 0.050). Among the different individual food groups, only a low consumption of whole dairy products showed a significant inverse association. The Mediterranean diet as a whole seems more important than each of its components in preventing the infection and symptoms of COVID-19.